Scoping review of brucellosis in Cameroon: Where do we stand, and where are we going? - Christopher G Laine; Abel Wade; H Morgan Scott; Rosina C Krecek; Angela M Arenas-Gamboa (PLoS ONE)
Brucellosis is a zoonotic disease known to be endemic to parts of western and sub-Saharan Africa. However, the epidemiology for humans and animals remains largely unknown in many of these countries with Cameroon being a typical example. Despite common knowledge that brucellosis affects livestock, the actual number of infected animals remains unknown. Through a scoping review, the current known status of the disease is described. The aim is to ascertain relevant and publicly accessible research and knowledge of human and animal brucellosis in the country, and to provide an overview of the factors associated with its known persistence. Seroprevalence has been estimated and published in 12 separate instances (1 human; 9 cattle; 1 human and cattle; and 1 that includes cattle, pigs, and small ruminants), between 1982 and 2020, in 9 of the country's 10 geopolitical regions. In 1983, Brucella abortus and B. melitensis were isolated in cattle, but no further bacterial isolation has been published since. The seroprevalence from 196 total humans has ranged between 5.6% and 28.1%, and between 3.0% and 30.8% for 14,044 total cattle. As there is no ongoing surveillance program, it is not currently possible to identify the specific Brucella spp. that are endemic to the country and its regions. There are sufficient agricultural systems of cattle, pigs, goats, and sheep to sustain the presence of multiple Brucella spp. Surveillance information is the cornerstone of epidemiologic decision making, and is needed to direct policy makers, public health authorities, and veterinary services to appropriate actions. A combination of serological and molecular based diagnostics for surveillance is necessary to identify, quantify, and direct the appropriate public health interventions. Cameroon has an opportunity to build public and animal health infrastructure, leading the way for central Africa in the management and future eradication of brucellosis.